Production Management Of “Panji Semirang” At Asean Panji Festival 2023 In Yogyakarta - Riqullah, Muhammad Raka; Agustina, Arinta; Pangestu, Jangkung Putra (Institut Seni Indonesia Yogyakarta, 2024)
ASEAN Panji Festival 2023 is an international festival involving countries in Southeast Asia. The story of Panji Semirang was the play chosen in the festival. The aim of this festival is to practice good things and provide a bridge to the community about the Panji story through several programs that are run. This research aims to determine the production management process carried out during the implementation of